Time effects of climate change mitigation strategies for second generation biofuels and co-products with temporary carbon storage. (20th January 2016) - Pourhashem, Ghasideh; Adler, Paul R.; Spatari, Sabrina
Abstract: Second generation biofuels offer a means of reducing greenhouse gas emissions and storing or delaying soil carbon emissions relative to petroleum-based fuels depending upon the strategy used to synthesize the biofuel and co-products. Unless mitigated, the soil organic carbon and nitrogen loss resulting from removing agricultural residues for biofuel production may cause life cycle greenhouse gas emissions to surpass national policy thresholds, and thus risk non-compliance with renewable fuel policy. Strategies to mitigate soil organic carbon loss such as using nutrient and carbon-rich, and stable land amendments will lead to time-variable greenhouse gas credits. Recent studies have argued for using time-dependent rather than time-averaged radiative forcing methods for biofuel greenhouse gas accounting but few life cycle assessment studies have examined the impact of time-varying emissions of soil organic carbon using the Intergovernmental Panel on Climate Change tier 3 models. This study applies a time-dependent radiative forcing approach to a 100-year time-series data set of life cycle greenhouse gas emissions for lignocellulosic ethanol that includes temporally variable soil greenhouse gas emissions. This study demonstrates that averaging soil emissions and neglecting the time when the sequestration or release occurs within a selected time horizon can lead to a 9% to over 80% overestimation of the magnitude of the effect of the mitigation strategy. This affirms that employing strategies to maintain soil organic carbon stock early within a biofuel program supports climate change mitigation. Such strategies would guide farmers to best manage soil carbon within the biofuel production life cycle. Time-dependent approaches underscore the need for early measures of greenhouse gas curtailment to support sustainable renewable biofuel and agricultural policy. Highlights: Removing agricultural residues for biofuel leads to time varying soil GHG emissions. Soil emissions contribute to biofuel life cycle emissions beyond biorefinery's lifetime. A time dependent model is used to account for the biofuel time varying soil emissions. Time dependent GHG accounting tests the effects of storage and emission lags. Neglecting time-varying emissions from soils introduces error in life cycle GHG accounting.